A COMPARATIVE STUDY OF THE QUALITATIVE CHANGES IN THE LEVELS OF IL-4 , IL-6 AND IL-10 AND THEIR RELATIONSHIP TO HEMATOLOGICAL PARAMETERS IN CHILDREN WITH E. VERMICULARIS INFECTION - Abbas, Marwa Ismail; Abdulhasan, Rawaa Sahib; Farhan, Zainab Mohammed; A. mohsein, Osama (PT. Antis International Publisher, 2024)
Background; Enterobiasis (pinworm infection) caused by Enterobius vermicularis is a common parasitic infection prevalent worldwide especially in children. It causes many important symptoms and can lead to digestive problems and lead to malnutrition in children. Aims of the study; Knowing the relationship between levels of cytokine and the severity of infection in children and the extent of the impact of the infection on the child’s health in Iraq. Methodology; A Case-control study included 100 children suffering from infection with the worm E.vermicularis. The ages of the participants ranged from 3 to 10 years. The study included 50 healthy children matched in age and sex to the patient group. 5 ml of blood was collected from each participant at Al-Haboubi Teaching Hospital and at Nasiriyah General Hospital for the period between 3/1/2024 to 10/3/2024. CBC assay using a Sysmex device. Interleukins were examined using enzyme-linked immunosorbent assay. Result; The results showed that there was no statistical significance in age among the participants. While the results of WBC and CRP were significantly high in the patient group, in contrast to PCV and Hb which were significantly low. While interleukin 4 and interleukin 6 results showed a significant increase in the patient group, while interleukin 10 showed a significant decrease. Conclusions; High levels of biomarkers, indicate the immune response that causes by infection with the worm. Anemia due to the pathophysiology of inhibiting appetite and lack of absorption in Intestines for nutrients.